On Orchestrating Service Function Chains in 5G Mobile Network - Dongcheng Zhao; Jing Ren; Rongping Lin; Shizhong Xu; Victor Chang (IEEE Access, 2019)
As two of the key technologies of 5G, fog-based radio access network and network function virtualization have become an important direction for the radio network architecture evolution. Virtual network functions (VNFs) compose the service function chain (SFC) in a particular order, and the mobile network users communicate with each other or service terminals through SFCs. For service providers, it is crucially important for efficient deploying/mapping SFCs into the 5G mobile network since the SFCs deployment problem is an NP-hard problem. In this paper, we propose the efficient SFCs deployment algorithms for solving this challenge with two main design goals: 1) minimizing the cost of link resource, i.e., minimizing the path length of the entire SFC by combining VNFs and mapping temporary links and 2) minimizing the cost of computing resources by using the existing virtual machines as much as possible while performing the same VNF. We model the SFCs deployment problem as an optimization problem by using ILP as well as devise the heuristic algorithms to make the tradeoff between these two conflicting design goals. From simulation results, we can see that the performance of our proposed algorithms is promising in terms of the total SFCs mapping cost, total links mapping cost, and blocking ratio.